Analisis Teori Pemimpin dalam Konteks Perkembangan Karakteristik Individu - Nurjanah, Putria Wati; Masduki, Yusron; Choirunnisa, Annisa; Felzuka, Inayah (Lembaga Yasin AlSys, 2023)
Leadership is an important aspect in various areas of life, a deeper understanding of how individual characteristics contribute to the emergence of effective leaders can help in the development of better leaders in the future. This article aims to analyze various leader theories that have been developed by leadership experts in the context of the development of individual characteristics. The method used in this research is library research. This data was collected using documentation techniques from scientific journal articles that have been published online and books that match the theme. This article explores classical and contemporary theories of leadership, such as Great Man theory, situational leadership theory, charismatic leadership theory, and transformational leadership theory. We also conduct a critical analysis of these theories, focusing on how they link the development of individual characteristics to a person's ability to be an effective leader. Through a better understanding of the correlation between individual factors and leadership, we hope this article can provide deeper insight into how leaders are born and develop.